ON THE TRAGIC DIFFEREND (Dilemmas of Lyotard — Dilemmas of Postmodernity) - Kwiek, Marek (My University, 1997)
One can get the impression that postmodern thought — together with the world of postmodernity that surrounds us — has been deprived of the tragic, being "flattened" or "de-dramatized"1. Postmodern thinkers are often reproached for depriving their world of unresolvable conflicts, of contradictions, reproached for making it simple and comprehensible (Richard Rorty may serve as a paradigmatic object of criticism that goes along these lines, perhaps not without some reason). The tragic is supposed to have disappeared from philosophy upon the arrival of the existentialist absurd and to have never come back; the world is supposed to have lost for ever its apocalyptic dimension... And yet, despite various diagnoses and readings critical of postmodernism, one can show in postmodern reflection such points in which there may be the (irreducible) tragic, whose dramatic character strikes us as if the world had not been totally disenchanted of katharsis... Let us consider as an example the philosophical thought of Jean-François Lyotard.
Keywords: le differend; Jean-Francois Lyotard; French intellectuals; philosophy and politics; political engagement; postmodernism; postmodern philosophy; French Nietzscheanism; Creon and Antigone; litigation; tragedy; G.W.F. Hegel; Phenomenology of the Mind; Oedipus; Richard Rorty; Postmodern Condition; Whar Is Postmodernism?